Digital Accounting and SAK EMKM: Driving MSMEs' Competitive Advantage and Accounting Performance in Bali - Ida Ayu Ratih Manuari; Ni Putu Yuria Mendra (AIBPM Publisher, 2026)
This study investigates the impact of SAK EMKM implementation, financial literacy, and digital accounting literacy on Business Accounting Performance, with Competitive Advantage as a mediating variable among 210 MSMEs in Bali. Using Structural Equation Modeling-Partial Least Squares (SEM-PLS), the research reveals that SAK EMKM implementation, financial literacy, and digital accounting literacy significantly and positively enhance Competitive Advantage. Furthermore, Competitive Advantage is found to strongly dictate accounting performance, acting as a vital mediator in the model. Notably, the strongest indirect effect is observed in the relationship between digital accounting literacy and performance, proving that technological synergy is the primary